A novel variant of COL6A3 c.6817-2(IVS27)A>G causing Bethlem myopathy: A case report - Li, Maohua; Huang, Jiandi; Liu, Min; Duan, Chunmei; Guo, Hong; Chen, Xiaoyan; Wang, Yue (Frontiers in Neurology, 2023)
Bethlem myopathy (BM) is a disease that is caused by mutations in the collagen VI genes. It is a mildly progressive disease characterized by proximal muscle weakness and contracture of the fingers, the wrist, the elbow, and the ankle. BM is an autosomal dominant inheritance that is mainly caused by dominant COL6A1, COL6A2, or COL6A3 mutations. However, a few cases of collagen VI mutations with bilateral facial weakness and Beevor's sign have also been reported. This study presents a 50-year-old female patient with symptoms of facial weakness beginning in childhood and with the slow progression of the disease with age. At the age of 30 years, the patient presented with asymmetrical proximal muscle weakness, and the neurological examination revealed bilateral facial weakness and a positive Beevor's sign. Phosphocreatine kinase was slightly elevated with electromyography showing myopathic changes and magnetic resonance imaging (MRI) of the lower limb muscles showing the muscle MRI associated with collagen VI (COL6)-related myopathy (COL6-RM). The whole-genome sequencing technology identified the heterozygous mutation c.6817-2(IVS27)A>G in the COL6A3 gene, which was in itself a novel mutation. The present study reports yet another case of BM, which is caused by the recessive COL6A3 intron variation, widening the clinical spectrum and genetic heterogeneity of BM.